2018 summer extreme temperatures in South Korea and their intensification under 3 °C global warming. (20th September 2019) - Im, Eun-Soon; Thanh, Nguyen-Xuan; Kim, Young-Hyun; Ahn, Joong-Bae
Abstract: With the acceleration in global warming, extreme hot temperatures have emerged as one of the most prominent risks. In this study, we characterize the unprecedented extreme temperatures that occurred in Korea in summer 2018, and attempt to explain how this locally observed extreme event can be interpreted in the context of 2 °C and 3 °C global warming above the pre-industrial level. To better resolve geographically diverse climate features and enhance confidence in future changes, three global projections are dynamically downscaled using three regional climate models that are customized over Korea and the systematic biases are statistically corrected using quantile mapping. In July and August 2018, abnormally high maximum temperatures (Tmax) were observed over the entire territory of South Korea. Beyond the increase of mean value, Tmax at individual stations departed significantly from the typical Gaussian distribution of climatological Tmax due to the dramatic changes in the extent and shape of upper tails. The distinct behaviors of Tmax that appeared in 2018 largely represent the statistical analog of the distribution pattern expected under 3 °C global warming based on fine-scale climate projections. This implies that statistically extremely rare events like that of summer 2018 will become increasingly normal if global average temperature is allowed to increase by 3 °C. More importantly, the extreme heat stress measured by the wet-bulb globe temperature is projected to intensify the risks to a level never before seen in contemporary climate. This study is timely and relevant to the need to identify how the globally aggregated warming target temperature can be disaggregated into regional impacts.